PMSM Model with Phase-to-Phase Short-Circuit and Diagnosis by ESA and EPVA - C. Bouchareb; MS. Nait-Said (Advances in Electrical and Electronic Engineering, 2016)
One of the most frequent faults in PMSM stator is the insulation failure due to the degradation of the main isolation in the motor winding. This paper is aimed at suggesting a dynamic model of PMSM with phase-to-phase fault based on an equivalent electric circuit model including the real form of back EMF. The faulty model is used for studying the machine behavior and extracting the fault signatures for diagnosis. Two diagnostic techniques the Spectral Analysis (ESA) and Extend Park's Vectors Approach (EPVA) based on frequency analysis are applied to detect this kind of fault.